The Influence Of Price And Distribution Channels On Purchasing Decisions For Surya Coklat 16 Cigarettes At Cv. Pasifik Ganisigaret, Gunungsitoli City - Laoli, Yenoria Suwarni; Zalukhu, Yuterlin; Bate'e, Maria Magdalena; Laia, Otanius (Universitas Dehasen Bengkulu, 2025)
This research is motivated by the widespread circulation of illegal cigarettes in local markets and distribution challenges in remote areas, which have led to declining sales of legal products such as Surya Coklat 16 cigarettes. The objective of this study is to analyze the influence of price and distribution channels on the purchasing decision of Surya Coklat 16 cigarettes at CV. Pasifik Ganisigaret in Gunungsitoli City. This research employs a quantitative approach with an associative method. Data were collected through questionnaires distributed to 35 respondents, using a Likert scale as the measurement tool. Data analysis involved validity and reliability tests, multiple linear regression, t-tests, and F-tests using SPSS version 25. The results showed that all items were valid and reliable. The multiple correlation coefficient of 0.887 indicates a very strong relationship between price and distribution channels with purchasing decisions. The obtained regression equation is Y = 14.528 + 0.476X₁ + 0.195X₂, with a coefficient of determination (R²) of 0.786, indicating that 78.6% of the variation in purchasing decisions is explained by the two independent variables. Partially, price has a significant and more dominant influence than distribution channels. Simultaneously, both variables significantly influence purchasing decisions. These findings are expected to serve as a useful reference for the company in developing more competitive and adaptive marketing strategies amidst the rise of illegal cigarette products.